A Naturalist's Guide to the Reptiles of India : Bangladesh, Bhutan, Maldives, Nepal, Pakistan and Sri Lanka - Das, Indraneil; Das, Abhijit (John Beaufoy Publishing Ltd, 2017)
Known as the Indian subcontinent and the Indian Region, south Asia is home to one of tropical Asia’s regions of the greatest biodiversity. The region includes the countries next to or in the proximity of the Indian Ocean, comprising Bangladesh, Bhutan, India, the Maldives, Nepal, Pakistan and Sri Lanka. The geographic barriers that impede faunal movement into or out of the area include oceans, mountains and floodplains, and justify the recognition of the region as a distinct biogeographic unit. South Asia is exceptionally diverse in reptiles (more than 700 species). This richness is linked to the large size of the area, covering about 4.4 million square kilometres, and its location at the crossroads of two distinctive biogeographic realms, the Palaearctic and the Oriental. Consequently, there is much greater species diversity here than in even larger areas, such as China, North America north of the Rio Grande River, and Europe east of the Ural Mountains. The fauna of the Indian region is comparable to several tropical regions in the Indo-Pacific and Neotropical regions, such as Indonesia, Australia, Colombia and Brazil.